Optical Diagnostics and Sensing XVII: Toward Point-of-Care Diagnostics 2017
DOI: 10.1117/12.2252620
|View full text |Cite
|
Sign up to set email alerts
|

In vivo preclinical verification of a multimodal diffuse reflectance and correlation spectroscopy system for sensing tissue perfusion

Abstract: In reconstructive surgery, impeded blood flow in microvascular free flaps due to a compromise in arterial or venous patency secondary to blood clots or vessel spasms can rapidly result in flap failures. Thus, the ability to detect changes in microvascular free flaps is critical. In this paper, we report progress on in vivo pre-clinical testing of a compact, multimodal, fiber-based diffuse correlation and reflectance spectroscopy system designed to quantitatively monitor tissue perfusion in a porcine model’s su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…A portion of the results was reported in Refs. 20 and 21. Here, we present findings from the expanded data set.…”
Section: Introductionmentioning
confidence: 92%
“…A portion of the results was reported in Refs. 20 and 21. Here, we present findings from the expanded data set.…”
Section: Introductionmentioning
confidence: 92%
“…The measurements were done on the artery, muscle and skin of the MF in a porcine model but only on two animals. A significant inconsistency in obtained measurements was noted and the authors concluded that further development work is needed 148,149 .…”
Section: Brief Description Of Monitoring Methodsmentioning
confidence: 99%